Empowering Farmers through Natural Fibre Composites: Sustainable Solutions for Modern Industries - Sandeep Bhardwaj; Rupali Sharma (Research Perspective on Biological Science Vol. 2, 2025)
Natural fibre composites are a class of materials that combine natural fibres with a polymer matrix to create a composite material with unique properties. These composites aim to harness the strengths of natural fibres while addressing some of the limitations of traditional synthetic composites. The use of natural fibres in composites is not a new concept. In fact, people have been using natural fibres mixed with other materials for centuries. Previously, farmers had limited choices to earn; only edible and cash crops were grown and used. But nowadays, other plantations excluding cash crops, offer a better alternative to earn their livelihood. The idea of combining two or more different materials resulting in a new material with improved properties has existed for ages. Fibre is a unit of matter characterized by flexibility, fineness, and a high ratio of length to thickness. Because fibres have a high surface-to-volume ratio, they can be extremely strong materials. The composite materials have the combined advantages of each individual material. For time immemorial, man has been using fibres along with a binder or matrix for stronger materials. The usage of plant fibres for strengthening and preventing bricks and pottery from cracking was practiced by the Pharaohs of Egypt and the ancient Incan and Mayan civilizations. The natural fibres are used due to their low cost, high specific modulus, lightweight, lower energy requirement means less wear and tear in processing, wide availability, biodegradability, and resistance to deforestation. The use of natural fibres as a reinforcing agent in both thermoset and thermoplastic polymer composites gained inroads from automotive, aerodynamic, to biomedical engineering materials. The main mechanical properties of natural fibre, while selecting the crop or plantation, will be flexural strength, compressive strength, tensile strength, and moisture abortion of the fibre. Biopolymers could be another frontier for natural fibres, for their vast variety available in plants. In conclusion, natural fibre would be an excellent opportunity for small farmers to set up natural fibre composites factories in their villages and surrounding areas, just to create new composite components to cater to the needs of different industries like construction, automobile, etc., instead of making a new composite material.